Psychometric evaluation of the Italian translation of the Gamblers' Beliefs Questionnaire. Issue 1 (2nd January 2016) - Marchetti, Daniela; Whelan, James P.; Verrocchio, Maria C.; Ginley, Meredith K.; Fulcheri, Mario; Relyea, George E.; Meyers, Andrew W.
Abstract: Italy has experienced a rapid growth in gambling accessibility, expenditures and problems. Gambling-related cognitive distortions are established risk factors for disordered gambling, although little is known about the role of gambling-related cognitive distortions among Italians. To establish a valid tool for assessing these distortions, an Italian version of the Gamblers' Beliefs Questionnaire (GBQ-I) was translated and psychometrically evaluated in a sample of 749. Eighty-five percent had gambled recently and 110 were identified as probable disordered gamblers. Good reliability, internal consistency and test-retest reliability were demonstrated. Concurrent, convergent and predictive validities also suggested that the GBQ-I is a valid and reliable measure for assessing gambling-related cognitive distortions among clinical and non-clinical Italian samples. Factor analysis explored the two-factor structure from the measures' initial validation but was unable to replicate it. The validation of this translation of the GBQ allows for future cross-cultural research on the role of cognitive distortions in the study and treatment of gambling problems.